Robotic-assisted versus laparoscopic radical prostatectomy: 12-month outcomes of the multicentre randomised controlled LAP-01 trial - Stolzenburg, Jens-Uwe; Holze, Sigrun; Arthanareeswaran, Vinodh-Kumar-Adithyaa; Neuhaus, Petra; Do, Hoang Minh; Haney, Caelán Max; Dietel, Anja; Truss, Michael C.; Stützel, Karin Daniela; Teber, Dogu; Hohenfellner, Markus; Rabenalt, Robert; et al. (European urology focus, 2022)
BACKGROUND: Recently, our LAP-01 trial demonstrated superiority of robotic-assisted laparoscopic radical prostatectomy (RARP) over conventional laparoscopic radical prostatectomy (LRP) with respect to continence at 3 mo. OBJECTIVE: To compare the continence, potency, and oncological outcomes between RARP and LRP in the 12-mo follow-up. DESIGN, SETTING, AND PARTICIPANTS: In this multicentre, randomised, patient-blinded controlled trial, patients referred for radical prostatectomy to four hospitals in Germany were randomly assigned (3:1) to undergo either RARP or LRP. OUTCOME MEASUREMENTS AND STATISTICAL ANALYSIS: Continence was assessed as a patient-reported outcome through validated questionnaires. Secondary endpoints included potency and oncological outcomes. Data were statistically analysed by bivariate tests and multivariable models. RESULTS AND LIMITATIONS: At 12 mo, follow-up data were available for 701 of 782 patients. Continence at 6 and 12 mo after surgery was better in RARP patients, however no longer statistically significant (p = 0.068 and 0.38, respectively). Patients who were potent at baseline and underwent nerve-sparing surgery reported significantly higher potency after RARP, as defined by the capability to maintain an erection sufficient for intercourse at 3 (p = 0.005), 6 (p = 0.018), and 12 mo (p = 0.013). There were no statistically significant differences in oncological outcomes at 12 mo. It is a limitation that the influence of different anastomotic techniques was not investigated in this study. CONCLUSIONS: Both LRP and RARP offer a high standard of therapy for prostate cancer patients. However, robotic assistance offers better functional outcomes in specific areas such as potency and early continence in patients who are eligible for nerve-sparing RP. PATIENT SUMMARY: We compared outcomes 12 mo after radical prostatectomy between robotic-assisted and conventional laparoscopy. Both methods were equivalent with respect to oncological outcomes. Better recovery of continence in patients with robotic-assisted surgery, which was observed at 3 mo, blurred up to 12 mo. A benefit of robotic-assisted surgery was also observed in potency.